(untitled) - Aronin, Miriam; 1952-; Pushies, Fred J. (New York, 2012)
Describes some acts of bravery and heroism performed by Air Force personnel in Afghanistan and Iraq.
Attacked! -- War in Iraq -- "Is there anybody in here?" -- Rescue at the Pentagon -- Courage under fire -- Giving his life -- The Warthog is hit -- Back to base -- Directing jets -- Danger on the rooftop -- "Definitely danger" -- "Heroes in our ranks".
Includes bibliographical references (p. 31) and index.
Keywords: Biography; United States; Air Force; Biography; United States; Air Force; United States; Airmen; Juvenile literature; Afghan War, 2001-; Juvenile literature; Iraq War, 2003-; United States; Airmen; Iraq War, 2003-; Juvenile literature; Afghan War, 2001-